Հանդաբերդի վանքի վերականգնման հայեցակարգը - Կիրակոսյան, Լյուբա (ԱրՊՀ հրատ․)
Благодаря комплексному исследованию Андабердского монастыря стало возможным представить концепцию реставрации ансамбля. Учитывая уровень сохранности памятника предлагается версия целостной реставрации, а для колокольни и главной церкви дается еще и реконструкция. Рассматривается возможность благоустройства окружающей среды. Due to the complex investigation of Andaberdsk monastery it became possible to introduce the restoration concept of the ensemble. Taking into consideration the preservation level of the monument, is proposed the complete restoration version, and a reconstruction is needed for the belfry and the main church. The possibility for the improvement of the environment is studied.
Keywords: Արցախ; Ճարտարապետություն